Cyclic electron flow, NPQ and photorespiration are crucial for the establishment of young plants of Ricinus communis and Jatropha curcas exposed to drought - Lima Neto, M. C. [UNESP]; Cerqueira, J. V.A.; da Cunha, J. R.; Ribeiro, R. V.; Silveira, J. A.G. (Wiley, 2017)
Although plant physiological responses to drought have been widely studied, the interaction between photoprotection, photorespiration and antioxidant metabolism in water-stressed plants is scarcely addressed. This study aimed to evaluate the physiological adjustments preserving photosynthesis and growth in two plant species with different tolerance to drought: Jatropha curcas and Ricinus communis. We measured stress indicators, gas exchange, photochemistry of PSII and PSI, antioxidant enzymes, cyclic electron flow and photorespiration. Physiological stress indicators associated with reduction in growth confirmed R. communis as sensitive and J. curcas as tolerant to drought. Drought induced loss of photosynthesis in R. communis, whereas J. curcas maintained higher leaf gas exchange and photochemistry under drought. In addition, J. curcas showed higher dissipation of excess energy and presented higher cyclic electron flow when exposed to drought. Although none of these mechanisms have been triggered in R. communis, this species showed increases in photorespiration. R. communis displayed loss of Rubisco content while the Rubisco relative abundance did not change in J. curcas under drought. Accordingly, the in vivo maximum Rubisco carboxylation rate (Vcmax) and the maximum photosynthetic electron transport rate driving RuBP regeneration (Jmax) were less affected in J. curcas. Both species displayed an efficient antioxidant mechanism by increasing activities of ascorbate peroxidase (APX) and superoxide dismutase (SOD). Overall, we suggest that the modulation of different photoprotective mechanisms is crucial to mitigate the effects caused by excess energy, maintaining photosynthetic apparatus efficiency and promoting the establishment of young plants of these two species under drought.
Keywords: Photochemical activity; photoprotection; photorespiration; photosynthesis; water deficit